2001
DOI: 10.1021/ie001149m
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Vaporization in a Fluidized Bed

Abstract: Feedstock injection in the riser is a critical step of the fluid catalytic cracking process. However, although a few models have been developed, no experimental study of the vaporization of droplets in a hot fluidized bed has been published. Experimental studies were thus conducted. Agglomeration of wet particles greatly increases the evaporation time. The first step was thus the study of the different agglomeration processes which may occur when liquid droplets are injected into a hot fluidized bed. There are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…1,2 It has been shown that improving the contact of injected liquid with fluidized particles increases the yield of valuable liquid products in both the fluid catalytic cracking process, where most of the liquid is vaporizable, and in the fluid coking process, where most of the liquid is not directly vaporizable, but must first be cracked to generate vaporizable fractions. 1,3 In the case of vaporizable liquids, liquid-solid agglomerates may or may not be formed, depending on the operating conditions, 4,5 while they always form with nonvaporizable liquids. 6 Bruhns et al 7 investigated the interaction between vaporizable liquid jets and fluidized solids in a pilot-scale re-actor operated at 120-180 8C.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It has been shown that improving the contact of injected liquid with fluidized particles increases the yield of valuable liquid products in both the fluid catalytic cracking process, where most of the liquid is vaporizable, and in the fluid coking process, where most of the liquid is not directly vaporizable, but must first be cracked to generate vaporizable fractions. 1,3 In the case of vaporizable liquids, liquid-solid agglomerates may or may not be formed, depending on the operating conditions, 4,5 while they always form with nonvaporizable liquids. 6 Bruhns et al 7 investigated the interaction between vaporizable liquid jets and fluidized solids in a pilot-scale re-actor operated at 120-180 8C.…”
Section: Introductionmentioning
confidence: 99%
“…However, a similar structure has been observed in coke from delayed cokers; therefore, this cannot be viewed as a proof of the formation of liquid layers. 5 Leclere et al 6 have developed a method to characterize the contact between a vaporizing liquid and a fluidized bed by measuring the vaporization rate of the injected liquid. Unfortunately, this method cannot be readily adapted to applications with a nonvaporizing liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid dispersion of wetted solids is essential in fluid coking and other fluidized bed processes, such as olefin polymerization cooled by liquid injection, , fluid catalytic cracking, some petrochemical reactors, solid agglomeration, , and particle coating . In such processes, the low-temperature zone that results from the liquid injection expands with an increasing liquid flow rate and shrinks with an increasing superficial gas velocity, , presumably because solid dispersion increases with an increasing superficial gas velocity, moderately in the bubbling fluidization regime and more strongly in the turbulent fluidization regime .…”
Section: Reactormentioning
confidence: 99%